Consumer protection in Muslim friendly hospitality services with special reference to travel agencies services - Hamidah binti Ayob (International Institute for Halal Research and Training, International Islamic University Malaysia, 2017)
Muslim friendly or Shari'ah compliant hospitality services have emerged in recent years as part of the development of global halal industry. Malaysia has become one of the key players in this fast-growing and lucrative market and has been rated the world's top Muslim-friendly holiday destination for the past few years by various rating agencies. As one of the most important service providers for tourism and travel related activities, the travel agencies play an important and essential role in worldwide tourism development and their role has been expanded in recent years with the global growth of Muslim friendly tourism and hospitality services. Despite this remarkable development, there have been many consumer complaints related to hospitality services in Malaysia. In fact, consumer claims against the travel agents were the top in the list of services cases filed in the Tribunal for Consumer Claims (TCC) for the past many years. In 2014, the TCC received 1,585 complaints against travel agencies especially related to umrah package. Thus the question arises as to whether the rights of Muslim travellers are well protected under the relevant laws in Malaysia. Adopting a doctrinal and content analysis methodology, the study aims to identify consumers' issues in relation to travel agencies services in Malaysia. The main focus is to examine the relevant framework which include relevant laws, regulations, guidelines, codes of ethics which are related to Muslim friendly travel agencies services. The laws including Tourism Industry Act 1992 and Tourism Industry (Tour Operating Business and Travel Agency Business regulations 1992), MATTA Code of Ethics and Malaysian Standard MS 2610:2015 Muslim Friendly Hospitality Services-requirements. The purpose is to analyse the adequacy of the existing consumer protection laws in protecting Muslim travellers. The study discovers the lacunae in the existing legal protection for consumers which renders the protection to be inadequate. Hence, the study proposes recommendations to improve and enhance protection for consumers in dealing with Muslim friendly travel agencies.